Failure to Enroll: The Blurring Rhetorical Power of Anonymizing Tools and Photographs in Making In/Visible Black Lives - Marin, Kellie (Surveillance & Society, 2024)
As Black Lives Matter (BLM) protests surged in response to the continued murders of black men and women, state surveillance practices, too, have increasingly monitored, tracked, and prosecuted protesters. Among the growing surveillance arsenal are facial recognition technologies (FRT), which authorities use to identify protesters, often leading to the mis/recognition of black and brown people, false arrests, and blacklisting from public spaces. In response to the prevalence of FRT, protesters and photographers are urging and employing anonymizing blurring technologies to evade state and citizen surveillance. I argue that these technologies materially and rhetorically disrupt the racialized surveillant gaze. I employ Simone Browne’s (2015) term “dark sousveillance” as a framework for understanding how blurring technologies enable evasion from state violence and promote ethical photography practices. Such practices challenge the relationship between whiteness and the law enforcement surveillance regime.